2021
DOI: 10.13189/ujaf.2021.090401
|View full text |Cite
|
Sign up to set email alerts
|

Interest Rates and Inflation as Determining Factors of Saving in Central Sulawesi Banks

Abstract: This study aims to analyze the effect of the Central Bank, which is in Indonesia presented by Bank Indonesia (BI) Rate and inflation rate on the savings rate at commercial banks in Central Sulawesi by using the analysis tools of autoregressive conditional heteroscedasticity (ARCH) and generalized autoregressive conditional heteroscedasticity (GARCH). The results of the analysis show that the BI Rate and inflation have significant effects on saving rate at commercial banks in Central Sulawesi. The importance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…While the interest rate fluctuations had a negative and insignificant effect on return on assets (Ibekwe, 2021). Study (Jaya A. H., et al, 2021) underscored the findings regarding the negative effect of interest rates on savings in contradiction with the general economic theory of Money. While (Naufal & John, 2021) confirmed that there was no significant effect of the interest rate on the performance of banks.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…While the interest rate fluctuations had a negative and insignificant effect on return on assets (Ibekwe, 2021). Study (Jaya A. H., et al, 2021) underscored the findings regarding the negative effect of interest rates on savings in contradiction with the general economic theory of Money. While (Naufal & John, 2021) confirmed that there was no significant effect of the interest rate on the performance of banks.…”
Section: Introductionmentioning
confidence: 73%
“…This provides support for the precautionary motives to save in the face of economic uncertainty. To evaluate the effect of the inflation rate on savings; The study of (Jaya, A. H., et al, 2021), (Naufal & John, 2021) showed that the level of inflation has no significant effect on the saving variable, and it has no significant impact on the performance of banks and bank deposits. According to (Jayawarsa, A.…”
Section: The Relationship Between the Inflation Rate (Cpi) And Deposi...mentioning
confidence: 99%